The potential energy profile of the decomposition of 1, 1-diamino-2, 2-dinitroethylene (FOX-7) in the gas phase. Issue 43 (1st November 2022) - Luo, Yuheng; Kang, Christopher; Kaiser, Ralf; Sun, Rui
Abstract : The decomposition products of 1, 1-diamino-2, 2-dinitroethylene (FOX-7) in the gas phase. Abstract : 1, 1-Diamino-2, 2-dinitroethene (FOX-7) is an energetic material with low sensitivity and high detonation performance, thus it has been considered as a potential replacement for traditional nitro-based energetic materials. In a recent publication (J. Phys. Chem. A, 2022, 126, 4747), the initial decomposition steps of FOX-7 were studied using reflectron time-of-flight mass spectrometry and infrared spectroscopy. The experimental study was complemented with quantum chemistry calculations, which demonstrated the gas phase potential energy surface to be indicative of the reaction process in the condensed phase. The computation in J. Phys. Chem. A, 2022, 126, 4747 focuses on the primary decomposition – but in this manuscript, the full decomposition pathway on the singlet surface, consisting of 54 intermediates and 37 transition states, is characterized at an unprecedented detail. The calculations show that the nitro group, instead of the amine group, is primarily responsible for the sensitivity and endothermicity of FOX-7 decomposition. This result sheds light on how to critically optimize the performance of FOX-7 and design the next generation of nitro-based energetic materials. A comprehensive roadmap, initiated from FOX-7, covers the chemical space of the entire decomposition thus providing a holistic demonstration of various key decomposition pathways leading to various small, gas phase products such as NO, NO2, NH2, CO2, and CO.